PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA ( Studi Pada Guru SMA Negeri 3 Pati Kabupaten Pati) - Mujiannie, 12.52.02.0068; Sunarto, Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2014)
This Study aims to test the influence of principal leadership ,teacher motivation on performance of SMA Negeri 3 Pati starch mediated job satisfaction. The specific objectives if this research is to examine the role of job satisfaction mediated the influence of principal leadership and motivation to performance of teachers. The usefulness of this study is to describe and extend previous research regarding the role of job satisfaction mediates the influence of leadership and motivation of teachers. This research using population teachers SMA Negeri 3 Pati as many as 70 teachers. The method of sampling in this research is with cencus techniques,i.e all the populations were sampled.Based of the results of the study can be summed up as follows :the leadership the principal has no effect on job satisfaction,positive and influential teacher motivation significantly to job satisfaction, leadership principals have no effect on performance of teacher, motivational positive and significant effect job on performance of teachers job satisfaction, positive and significant effect on performance of teachers, that the direct influence of motivation on performance more effectively than the indirect influence so that job satisfaction does not mediate the effects of motivation on performance of teachers. Keywords : motivation,principal leadership, job satisfaction and performance of teachers